2006
DOI: 10.1590/s1413-80502006000100008
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa de Curva de Phillips para o Brasil com preços desagregados

Abstract: Este artigo realiza estimativas de Curvas de Phillips para o Brasil a partir de dados de preços desagregados utilizando-se o método de mínimos quadrados em três estágios. Dessa forma é possível aliviar o problema da baixa disponibilidade de dados disponível para a economia brasileira e realizar uma análise mais detalhada da dinâmica da inflação. As regressões são realizadas com a utilização da capacidade da indústria, tal como divulgada pela FGV, como proxy para o efeito do ciclo econômico sobre a inflação, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
27

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 8 publications
1
10
0
27
Order By: Relevance
“…The results showed that there is a negative and statistically significant relationship between inflation and unemployment, overcoming a common empirical difficulty with the appropriate measure of marginal cost to be included in the Phillips curve [e.g. Schwartzman (2006), Minella et al (2003), Areosa and Medeiros (2007)]. In addition, we found evidence of high real wage rigidity in the recent low inflation period following the edition of the Real plan.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The results showed that there is a negative and statistically significant relationship between inflation and unemployment, overcoming a common empirical difficulty with the appropriate measure of marginal cost to be included in the Phillips curve [e.g. Schwartzman (2006), Minella et al (2003), Areosa and Medeiros (2007)]. In addition, we found evidence of high real wage rigidity in the recent low inflation period following the edition of the Real plan.…”
Section: Discussionmentioning
confidence: 66%
“…The contribution of the paper is to show that the new Phillips curve fits the Brazilian data very well, as opposed to alternative versions estimated by Schwartzman (2006), Minella et al (2003), Areosa and Medeiros (2007), among others. One difficulty faced by those authors was with the proxy for marginal cost, which shows up with sign opposite to expected or statistically non-significant in the estimation.…”
Section: Introductionmentioning
confidence: 96%
“…Portugal et al (1999), Lima (2003), Fasolo & Portugal (2004), Muinhos (2004), Araujo & e Guillén (2004), Alves & Areosa (2005), Correa & Minella (2005), Schwartzman (2006), entre outros, são alguns autores com importantes contribuições nessa área. 2 A Tabela 1 abaixo mostra um breve apanhado de resultados para a economia brasileira.…”
Section: Introductionunclassified
“…Schwartzman (2006) estimates a Phillips curve using industrial capacity utilization data to address the fact that the output gap is not observable. Fasolo and Portugal (2004) adapt a NKPC for Brazil based on the NAIRU, emphasizing expectations formation.…”
Section: Related Literaturementioning
confidence: 99%